2020
DOI: 10.1155/2020/8854498
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Deaths due to Obstetric Haemorrhage in Dodoma Regional Referral Hospital, Tanzania

Abstract: Background. Despite the availability of comprehensive emergency obstetric care at Dodoma Regional Referral Hospital, deaths due to obstetric haemorrhage are still high. This study was carried out to analyse the circumstances that had caused these deaths. Methods. A retrospective review of all files of women who had died of obstetric haemorrhage from January 2018 to December 2019 was made. Results. A total of 18,296 women gave birth at DRRH; out of these, 61 died of pregnancy-related complications of the deceas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Almost 30% of cases presented in state of shock at the time of admission resulting in delayed intervention and hence adverse outcome. It was similar to the ndings from other studies done in developing countries(8)( 13) (14).…”
Section: Discussionsupporting
confidence: 92%
“…Almost 30% of cases presented in state of shock at the time of admission resulting in delayed intervention and hence adverse outcome. It was similar to the ndings from other studies done in developing countries(8)( 13) (14).…”
Section: Discussionsupporting
confidence: 92%
“…The study also demonstrated that the risk of dying due to the adverse outcomes of obstetric hemorrhage was lower at health facilities than at other places of death (home and on transit). The finding was coherent with studies conducted in Tanzania [ 72 ] and India [ 73 ]. One possible explanation would be the absence of life-saving assistance during referrals such as the Non-Pneumonic Anti-Shock Garment (NASG), which is one of the highly recommended lifesaving supplies for women with active maternal bleeding [ 74 ].…”
Section: Discussionsupporting
confidence: 89%
“…A study carried out in Israel stated that 70% and 59.2% of pregnant women suffered severe and extremely severe anxiety regarding fetal health and their exposure to virus infection, respectively (Taubman-Ben-Ari et al, 2020). In Belgium, serious depression symptoms and severe anxiety were reported in 25.3% and 8.4% of pregnant women during the pandemic period, respectively (Ceulemans et al, 2020). The increased depression, anxiety, and stress levels of pregnant women during the pandemic period have also caused a change in their obstetric decisions.…”
Section: Discussionmentioning
confidence: 99%